2012
DOI: 10.1179/1753807612y.0000000009
|View full text |Cite
|
Sign up to set email alerts
|

Promoters and barriers in hospital team communication. A focus group study

Abstract: Purpose: Poor teamwork and communication in healthcare teams have been correlated to adverse events and higher patient morbidity and mortality. However, detailed insight into the link between team communication and medical error is still lacking. The objective of this study is to identify the common characteristics of team communication among multiprofessional teams at four Danish acute care university hospitals. Method: Four focus group interviews with multiprofessional hospital teams (N = 24). Results: Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 28 publications
3
28
0
4
Order By: Relevance
“…A recent prospective observational study of over 400 communication events in one ED revealed more than 22 communication failures, with nurse handover reports being the most problematic (Bagnasco et al , ). This is similar to the findings of Costa () and Rabol et al (). Errors in documenting patient care were also common (Bagnasco et al , ).…”
supporting
confidence: 93%
“…A recent prospective observational study of over 400 communication events in one ED revealed more than 22 communication failures, with nurse handover reports being the most problematic (Bagnasco et al , ). This is similar to the findings of Costa () and Rabol et al (). Errors in documenting patient care were also common (Bagnasco et al , ).…”
supporting
confidence: 93%
“…The differences between N‐ANTS and ANTS may also be related to differences in professional and/or national culture. In Denmark the power distance is low . Consequently, nurses may find it relatively easy to speak up to the team when in doubt or having concerns .…”
Section: Discussionmentioning
confidence: 99%
“…They cite the egalitarian society of Denmark as a potential cause and point out structural issues that hint at the effect of the hidden curriculum: salaries are fairly similar between nurses and physicians. 4 We recognize that the majority of studies in this area cite a steep hierarchy as a significant influence in healthcare. It seems likely that the themes that emerged from our data may be relevant to practice in many contexts in North America and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…3 Perioperative teamwork exists within a context of both explicit and implicit hierarchies. 4 There are multiple power gradients within and between different professions and medical specialties. For instance, while there is a clear line of command between attending anesthesiologists and their residents, there may be a less formal status asymmetry between anesthesia and nursing (although the hierarchy may be quite clear to the individuals in the team) and more fluid power relations between surgery and anesthesia, depending on the individual physicians and the clinical context.…”
Section: Résumémentioning
confidence: 99%